Narrativas frente a la modificación del proyecto de vida y las relaciones interpersonales del cuidador informal según las fases de la enfermedad de Alzheimer - Calderon Rojas, Yeimin Adriana; Roa Leyton, Jeraldine Yulied (Universidad Antonio Nariño, 2025)
This research aimed to describe the narratives surrounding the modification of life projects and interpersonal relationships among a group of informal caregivers of individuals in various stages of Alzheimer's disease. The study was conducted within a qualitative methodological framework, utilizing a narrative design with a descriptive scope.The population consisted of ten informal caregivers of people with Alzheimer's, residing in Bogotá, who participated in three focus groups through unstructured interviews.